2004
DOI: 10.1016/s0960-0779(04)00239-5
|View full text |Cite
|
Sign up to set email alerts
|

Periodic orbit theory of two coupled Tchebyscheff maps

Abstract: Coupled map lattices have been widely used as models in several fields of physics, such as chaotic strings, turbulence, and phase transitions, as well as in other disciplines, such as biology (ecology, evolution) and information processing. This paper investigates properties of periodic orbits in two coupled Tchebyscheff maps. Then zeta function cycle expansions are used to compute dynamical averages appearing in Beck's theory of chaotic strings. The results show close agreement with direct simulation for most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In complement to these results, we would like to mention that estimates on the topological entropy in a CML of 2 sites with Tchebyscheff individual maps have been obtained in [DL05] by using periodic orbit theory.…”
Section: Introductionmentioning
confidence: 67%
“…In complement to these results, we would like to mention that estimates on the topological entropy in a CML of 2 sites with Tchebyscheff individual maps have been obtained in [DL05] by using periodic orbit theory.…”
Section: Introductionmentioning
confidence: 67%
“…In this paper we show that the answer is given by Chebyshev maps of N -th order. These are conjugated to the shift of N symbols by means of a cosine function, and have been subject of many previous papers [9,10,11,12,13]. We will show that any other conjugating function produces more higher-order correlations.…”
Section: Introductionmentioning
confidence: 82%
“…We now study spatially coupled systems [11,12,17,26] and investigate how the correlation patterns are modified. As the simplest model, consider a (periodic) lattice with just two sites that consists of two coupled 2nd-order ordinary Chebyshev maps:…”
Section: Cmls Of Two Sitesmentioning
confidence: 99%
“…In Refs. [19,20] weakly coupled N-th order Chebyshev maps [18,24,25,26,27] were studied and it was shown that certain scaling properties with respect to the coupling a can be calculated perturbatively. However, the fine structure of the parameter dependence of important observables of the chaotic string, such as the self energy or vacuum expectation value, could not be explained by these perturbative methods.…”
Section: Introductionmentioning
confidence: 99%